Electrode assembly and lithium secondary battery comprising same

By using a multi-layer coating formed between the positive electrode and the negative electrode in the lithium secondary battery, an electrode assembly containing oxide solid electrolyte particles and ceramic particles, the lithium secondary battery has been solved by using a multi-layer coating formed between the positive electrode and the negative electrode, and the electrode assembly containing oxide solid electrolyte particles and ceramic particles. The ignition of lithium secondary battery at high temperatures and poor electrolyte impregnation properties is solved. Problem, achieving higher battery safety and performance.

CN119213604APending Publication Date: 2024-12-27LG ENERGY SOLUTION LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380040390.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-20
Filing Date
2023-12-21
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Lithium secondary batteries have a risk of fire in high temperature environments, and the flame-retardant electrolyte is difficult to immerse into conventional separators, resulting in uneven reactions between the electrodes and the electrolytes and short-circuit problems, affecting battery performance.

Method used

The electrode assembly is adopted that forms more than two coatings between the positive electrode and the negative electrode. The coating contains oxide solid electrolyte particles and ceramic particles to ensure good impregnation and high temperature stability of the flame retardant electrolyte, and select suitable particles and polymerization. material to improve battery safety and performance.

Benefits of technology

It effectively prevents the lithium secondary battery from short circuiting and ignition at high temperatures, improves the high temperature safety of the battery and the electrolyte impregnation properties, thereby improving the capacity, output and life characteristics of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213604A_ABST
    Figure CN119213604A_ABST
Patent Text Reader

Abstract

The present invention relates to an electrode assembly including a positive electrode, a negative electrode, and a coating layer between the positive electrode and the negative electrode, in which the coating layer is formed in two or more layers in a stacking direction of the positive electrode and the negative electrode, in which the coating layer includes a first coating layer in facing contact with the negative electrode and a second coating layer not in facing contact with the negative electrode, the first coating layer contains any one type of particles selected from the following i) to iii), when the first coating layer contains i) or ii), the second coating layer contains iii), and when the first coating layer contains iii), the second coating layer contains i) or ii): i) oxide-based solid electrolyte particles and ceramic particles having an absolute value of zeta potential of 25 mV or more, ii) oxide-based solid electrolyte particles, and iii) ceramic particles having an absolute value of zeta potential of 25 mV or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0181062 filed on December 21, 2022, Korean Patent Application No. 10-2023-0057709 filed on May 3, 2023, and Korean Patent Application No. 10-2023-0187354 filed on December 20, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.

[0003] The present invention relates to an electrode assembly and a lithium secondary battery including the same. [Background Technology]

[0004] Recently, as the application fields of lithium secondary batteries have rapidly expanded to energy storage power sources for large-area devices such as automobiles and power storage devices, and power sources for electronic equipment such as electricity, electronics, communications and computers, the demand for lithium secondary batteries with high capacity, high output, long life and high stability has increased.

[0005] Generally, a lithium secondary battery comprises a positive electrode, a negative electrode, a separator inserted between the positive electrode and the negative electrode, an organic solvent, etc. Since the positive electrode is structurally unstable when charged and generates oxygen, which has a high risk of fire, people have been trying to research and develop methods to improve the safety of lithium secondary batteries.

[0006] A separator is used to ensure electrical insulation between the positive electrode and the negative electrode, and a film made of polyolefin is generally used. However, polyolefin separators tend to shrink in high temperature environments, so they cannot form insulation between the positive electrode and the negative electrode. When electrical insulation cannot be formed between the positive electrode and the negative electrode, a short circuit may occur, and the short circuit may interact with the oxygen generated by the unstable positive electrode to cause a fire. In other words, when a short circuit occurs in a charged lithium secondary battery in a high temperature environment, there may be a problem of a lithium secondary battery catching fire.

[0007] Furthermore, it is well known that the electrolyte of a lithium secondary battery contains a highly volatile and flammable solvent, and thus has the problem of being easily ignited.

[0008] To solve this problem, all-solid-state batteries using flame-retardant electrolytes containing flame-retardant solvents may be a solution, but the problem is that this flame-retardant electrolyte cannot be well impregnated into conventional separators, and the battery performance is poor due to low ion conductivity and high interface resistance between electrolyte particles. In addition, if the electrolyte cannot be well impregnated into lithium secondary batteries, there is a problem of uneven reaction between the electrode and the electrolyte, resulting in dendrites and causing short circuits.

[0009] Therefore, in order to solve these problems, attempts have been made to research and develop methods capable of maintaining and enhancing various properties while improving the stability of lithium secondary batteries. [Summary of the invention]

[0010] [Technical issues]

[0011] Therefore, the present invention aims to solve the above problems, and an object of the present invention is to provide an electrode assembly that not only has excellent high-temperature safety to prevent fire but also has high electrolyte impregnation to have excellent battery performance, and a lithium secondary battery including the same.

[0012] [Technical solution]

[0013] According to one embodiment of the present invention, there is provided an electrode assembly, comprising:

[0014] A positive electrode, a negative electrode, and a coating between the positive electrode and the negative electrode,

[0015] The coating is formed into two or more layers in the stacking direction of the positive electrode and the negative electrode.

[0016] Wherein, the coating comprises a first coating in contact with the negative electrode and a second coating not in contact with the negative electrode, the first coating contains any one of the particles selected from the following i) to iii), when the first coating contains i) or ii), the second coating contains iii), when the first coating contains iii), the second coating contains i) or ii):

[0017] i) oxide solid electrolyte particles and ceramic particles with a zeta potential of 25 mV or more,

[0018] ii) oxide-based solid electrolyte particles, and

[0019] iii) Ceramic particles having an absolute value of zeta potential of 25 mV or more.

[0020] Among them, the oxide solid electrolyte particles may include one or more lithium metal oxides or lithium metal phosphates selected from Nasicon-type solid electrolytes, Lisicon-type solid electrolytes, garnet-type solid electrolytes, perovskite-type solid electrolytes and LiPON-type solid electrolytes. More specifically, the oxide solid electrolyte particles may include one or more selected from the group consisting of LAGP (lithium aluminum germanium phosphate) compounds, LLZO (lithium lanthanum zirconium oxide) compounds, LATP (lithium aluminum titanium phosphate) compounds, LLZTO (lithium lanthanum zirconium tantalum oxide) compounds, LLTO (lithium lanthanum titanium oxide) compounds, LSTP (lithium silicon titanium phosphate) compounds and LGPO (lithium germanium phosphate) compounds.

[0021] In addition, the ceramic particles may include one or more selected from the group consisting of BN (boron nitride), boehmite, Al2O3, TiO2, Fe2O3, SiO2, ZrO2, Co3O4, SnO2, NiO, ZnO, V2O5, LiF and MnO. Specifically, the ceramic particles may include one or more selected from the group consisting of BN (boron nitride), boehmite, Al2O3 and LiF.

[0022] The second coating layer may be in contact with the positive electrode.

[0023] The first coating layer may include iii), and the second coating layer may include i) or ii).

[0024] On the other hand, one or more of the first coating and the second coating may further contain polymer particles having an absolute value of a Zeta potential of 25 mV or more, wherein the polymer particles may include one or more selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl methacrylate (PMMA), polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate and polyethylene terephthalate.

[0025] In addition, the electrode assembly further includes a separator, and the second coating layer may be in contact with the positive electrode, the separator, or the positive electrode and the separator. In this case, the first coating layer may include iii), and the second coating layer may include i) or ii).

[0026] In addition, in this case, the first coating layer and the second coating layer may contain polymer particles having an absolute value of Zeta potential of 25 mV or more, wherein the polymer particles may include one or more selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl methacrylate (PMMA), polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate and polyethylene terephthalate.

[0027] On the other hand, the coating layer may further include one or more additives selected from the group consisting of a binder and a dispersant, respectively.

[0028] The thickness of the coating can be from 1 micron to 30 microns respectively.

[0029] According to another embodiment of the present invention, a lithium secondary battery including the electrode assembly, an electrolyte, and a battery case is provided.

[0030] At this time, the electrolyte may be a flame retardant electrolyte including a flame retardant solvent having a flash point of 100° C. or more or having no flash point and a lithium salt.

[0031] The flame retardant solvent may include one or more compounds selected from sulfone compounds, nitrile compounds, phosphoric acid compounds and fluorocarbonate compounds, and the lithium salt may include, for example, LiN(SO2CF3)2. [Drawings]

[0032] Figure 1 An electrode assembly according to one embodiment of the present invention is schematically shown.

[0033] Figure 2 An electrode assembly according to another embodiment of the present invention is schematically shown.

[0034] Figure 3 An electrode assembly according to another embodiment of the present invention is schematically shown.

[0035] Figure 4 An electrode assembly according to another embodiment of the present invention is schematically shown.

[0036] Figure 5 An electrode assembly according to another embodiment of the present invention is schematically shown.

[0037] Figure 6 An electrode assembly according to another embodiment of the present invention is schematically shown.

[0038] Figure 7 An electrode assembly according to another embodiment of the present invention is schematically shown. [Specific implementation method]

[0039] Hereinafter, the terms or words used in this specification and claims should not be understood as being limited to conventional terms or dictionary terms, but should be interpreted in the meaning and concept consistent with the technical idea of ​​the present invention based on the principle that the inventor can appropriately define the concept of the term to appropriately describe his own invention in the best manner.

[0040] Unless otherwise defined, all terms (including technical terms and scientific terms) used in this specification may be the meanings commonly understood by those of ordinary skill in the art to which the present invention belongs. In addition, unless otherwise clearly defined, terms defined in commonly used dictionaries should not be idealized or over-interpreted.

[0041] The terms used herein are used to describe the embodiments, but do not limit the concepts of the present invention. In the specification, unless the context clearly indicates otherwise, the singular includes the plural. The terms "include" and / or "comprising" used herein do not exclude the presence or addition of one or more elements other than those described.

[0042] Throughout the specification, unless explicitly described to the contrary, the word “comprise” and variations such as “include” or “comprising”, will be understood to imply the inclusion of stated elements but not the exclusion of any other elements.

[0043] As used herein, "zeta potential" is an indicator of the degree of surface charge of particles. For example, the zeta potential of the particles in the present invention can be measured by electrophoretic light scattering using a dynamic light scattering device. Specifically, the zeta potential value of the polymer particles or ceramic particles contained in the coating of the present invention can be measured by electrophoretic light scattering using a dynamic light scattering device. For example, the zeta potential value can be measured after dispersing the polymer particles or ceramic particles in a solvent such as water or alcohol without a dispersant.

[0044] Hereinafter, the embodiments described herein and the structures shown in the accompanying drawings are merely the most preferred embodiments of the present invention and do not represent the entire spirit of the present invention. Therefore, it should be understood that various equivalents and modifications that can replace these embodiments and structures may exist when the present application is submitted.

[0045] According to an embodiment of the present invention, there is provided an electrode assembly, comprising:

[0046] A positive electrode, a negative electrode, and a coating between the positive electrode and the negative electrode,

[0047] The coating is formed into two or more layers in the stacking direction of the positive electrode and the negative electrode.

[0048] Wherein, the coating comprises a first coating in contact with the negative electrode and a second coating not in contact with the negative electrode, the first coating contains any one of the particles selected from the following i) to iii), when the first coating contains i) or ii), the second coating contains iii), when the first coating contains iii), the second coating contains i) or ii):

[0049] i) oxide solid electrolyte particles and ceramic particles with a zeta potential of 25 mV or more,

[0050] ii) oxide-based solid electrolyte particles, and

[0051] iii) Ceramic particles having an absolute value of zeta potential of 25 mV or more.

[0052] <Coating>

[0053] As the oxide-based solid electrolyte particles, any solid electrolyte having a lithium ion source containing lithium in its structure and in the form of a lithium metal oxide or a lithium metal phosphate can be used.

[0054] Specific examples thereof include one or more lithium metal oxides or lithium metal phosphates selected from Nasicon type solid electrolytes, Lisicon type solid electrolytes, garnet type solid electrolytes, perovskite type solid electrolytes and LiPON type solid electrolytes. More specific examples include one or more selected from the group consisting of LAGP (lithium aluminum germanium phosphate) compounds, LLZO (lithium lanthanum zirconium oxide) compounds, LATP (lithium aluminum titanium phosphate) compounds, LLZTO (lithium lanthanum zirconium tantalum oxide) compounds, LLTO (lithium lanthanum titanium oxide) compounds, LSTP (lithium silicon titanium phosphate) compounds and LGPO (lithium germanium phosphate) compounds.

[0055] Among them, from the perspective of accelerating the desolvation of lithium ions at the interface between the active material layer and the coating layer, improving the ionic conductivity and output of the lithium secondary battery, Nasicon-type solid electrolytes or garnet-type solid electrolytes can be preferably used. More specifically, Nasicon-type solid electrolytes such as LAGP-type compounds or LATP-type compounds can be suitably used.

[0056] When the coating layer contains oxide solid electrolyte particles, this is preferred because the oxide solid electrolyte particles themselves have affinity with the electrolyte and thus can reduce the resistance.

[0057] The average particle size (D50) of the oxide-based solid electrolyte particles may be 50 nanometers to 10 micrometers, specifically 50 nanometers to 5 micrometers, and more specifically 50 nanometers to 1 micrometer.

[0058] If the average particle size exceeds the above range and is too small, aggregation between particles may occur due to reduced dispersibility. On the contrary, if the average particle size is too large, the pores of the coating may be too large, and lithium dendrites may be easily formed through the pores, so it is not preferred.

[0059] When the average particle size satisfies the above range, the lithium ion conductivity of the coating layer can be improved, thereby reducing the resistance and exhibiting improved secondary battery performance.

[0060] The absolute value of the zeta potential of the ceramic particles can be 25mV or more, specifically 35mV or more, and more specifically 45mV or more. When the absolute value of the zeta potential satisfies the above range, even if the flame retardant electrolyte is applied to a lithium secondary battery containing the electrode of the present invention, the flame retardant electrolyte can be easily impregnated into the coating, so that a uniform reaction can occur in the entire electrode, thereby improving the performance of the lithium secondary battery, such as capacity, output, and life characteristics.

[0061] Specific examples of ceramic particles include one or more selected from the group consisting of BN (boron nitride), boehmite, Al2O3, TiO2, Fe2O3, SiO2, ZrO2, Co3O4, SnO2, NiO, ZnO, V2O5, LiF and MnO, but are not limited thereto. Specifically, the ceramic particles may include one or more selected from the group consisting of BN (boron nitride), boehmite, Al2O3 and LiF, and more specifically, may include BN (boron nitride) and boehmite.

[0062] The average particle size (D50) of the ceramic particles can be 30 nanometers to 5 micrometers, specifically 50 nanometers to 3 micrometers, more specifically 50 nanometers to 1 micrometer, which is less than the thickness of the coating. In addition, compared with the thickness of the coating, it can be less than 1 / 100 to 1 / 3 of the total thickness of the coating.

[0063] When the average particle size of the ceramic particles is 50 When the average particle size is smaller, the particles aggregate due to reduced dispersibility; if the average particle size is larger, there is a problem that a lithium dendrite growth path may be formed.

[0064] As used herein, the average particle size D 50 It refers to the particle size when the cumulative volume of particles in the particle size distribution curve reaches 50%. 50 The measurement can be performed using, for example, laser diffraction, which can generally measure particle sizes from the submicron range to several millimeters and can obtain results with high reproducibility and high resolution.

[0065] According to the present invention, the coating layer must be in contact with the negative electrode surface. When the coating layer is formed of two or more layers, in addition to the first coating layer in contact with the negative electrode surface, the second coating layer may be in contact with the positive electrode surface.

[0066] In this case, as described above, the first coating may contain particles selected from i) to iii), when the first coating contains i) or ii), the second coating may contain iii), when the first coating contains iii), the second coating may contain i) or ii). However, the first coating faces the negative electrode, so if a side reaction with the negative electrode occurs in the voltage region of the negative electrode, the efficiency may be reduced, which may lead to a reduction in capacity and energy density. In this regard, it is preferred to use a material with less side reactions with the negative electrode. Therefore, it is preferred to include ceramic particles with an absolute value of zeta potential of 25mV or more in iii) with relatively no side reactions, specifically, one or more ceramic particles selected from the group consisting of boron nitride (BN), boehmite, Al2O3 and LiF.

[0067] At this time, if the second coating causes a side reaction with the positive electrode within the voltage range of the positive electrode, the efficiency may be reduced, and a decrease in capacity and energy density may occur. Therefore, it is preferred to use a material with less side reactions with the positive electrode. However, since the positive electrode surface is relatively more stable than the negative electrode surface, side reactions are not a major problem, so a material that is more conducive to improving performance can be used, and an oxide-based solid electrolyte can be contained, so i) or ii) can be included.

[0068] More specifically, the first coating layer comprises one or more ceramic particles selected from the group consisting of boron nitride (BN), boehmite, Al2O3 and LiF, wherein the absolute value of the Zeta potential is 25 mV or more. The second coating layer may comprise one or more selected from the group consisting of boron nitride (BN), boehmite, Al2O3, LiF and oxide-based solid electrolyte particles.

[0069] Meanwhile, one or more of the first coating layer and the second coating layer may further include polymer particles each having an absolute value of zeta potential of 25 mV or more.

[0070] Here, the polymer particles may be particles with surface charges. Alternatively, the polymer particles may include particles with surface charges and particles without surface charges. The surface charges may be present on the particles themselves, or may be formed by physical or chemical surface treatment.

[0071] Here, the absolute value of the zeta potential of the polymer particles may be 25 mV or more, specifically 35 mV or more, and more specifically 45 mV or more. When the absolute value of the zeta potential satisfies the above range, even if the flame retardant electrolyte is applied to a lithium secondary battery containing an electrode of the present invention, the flame retardant electrolyte can be easily impregnated into the coating, so that a uniform reaction can occur in the entire electrode, thereby improving the performance of the lithium secondary battery, such as capacity, output, and life characteristics.

[0072] Specifically, the polymer particles may include one or more selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl methacrylate (PMMA), polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate and polyethylene terephthalate, but are not limited thereto. Specifically, the polymer particles may include polymethyl methacrylate.

[0073] The average particle size (D50) of the polymer particles can be 50 nanometers to 3 micrometers, specifically 50 nanometers to 2 micrometers, more specifically 50 nanometers to 1.5 micrometers, which is less than the thickness of the coating. In addition, compared with the thickness of the coating, it can be less than 1 / 100 to 1 / 3 of the thickness of the coating.

[0074] When the average particle size (D50) of the polymer particles meets the above numerical range, the dispersibility of the particles contained in the coating can be improved, and pores of appropriate size are uniformly formed in the coating, thereby improving the mobility of lithium ions. On the other hand, when the average particle size (D50) of the polymer particles is less than 50 nanometers, due to the reduced dispersibility of the particles, aggregation will occur between the particles, and the pores will be blocked by the aggregated particles, thereby reducing the mobility of lithium ions and increasing the resistance. If the average particle size (D50) of the polymer particles is greater than 3 microns, there is a problem of the possible formation of a lithium dendrite growth path as described above.

[0075] When the oxide-based solid electrolyte particles and / or ceramic particles are included together with the polymer particles, the content of the polymer particles may be 10 wt % to 40 wt %, specifically 20 wt % to 40 wt %, more specifically 20 wt % to 30 wt % of the total weight of each coating layer.

[0076] Meanwhile, in the coating in which the oxide solid electrolyte particles and the ceramic particles are mixed, the oxide solid electrolyte particles and the ceramic particles may be mixed in a weight ratio of 9:1 to 1:9, specifically, in a weight ratio of 7:3 to 3:7.

[0077] When the above range is satisfied, the coating is most excellent in pore uniformity, heat resistance and electrolyte impregnation.

[0078] In another specific embodiment, the electrode assembly may further include a separator, in which case the second coating may be in facing contact with the positive electrode, the separator, or both the positive electrode and the separator.

[0079] In this case, as described above, the first coating layer may include particles selected from i) to iii), when the first coating layer includes i) or ii), the second coating layer may include iii), when the first coating layer includes iii), the second coating layer may include i) or ii), however, for the above reasons, the first coating layer facing the negative electrode may include iii), the second coating layer may include i) or ii), most specifically, the first coating layer includes one or more ceramic particles selected from the group consisting of boron nitride (BN), boehmite, Al2O3 and LiF, and the second coating layer preferably includes one or more selected from the group consisting of boron nitride (BN), boehmite, Al2O3, LiF and oxide-based solid electrolyte particles. At the same time, at this time, one or more of the first coating layer and the second coating layer may also include polymer particles each having an absolute value of zeta potential of 25 mV or more.

[0080] Here, the polymer particles may be particles with surface charges. Alternatively, they may include particles with surface charges and particles without surface charges. The surface charges may be present on the particles themselves, or may be formed by physical or chemical surface treatment.

[0081] Here, the absolute value of the zeta potential of the polymer particles can be 25mV or more, specifically 35mV or more, and more specifically 45mV or more. When the absolute value of the zeta potential satisfies the above range, even if the flame retardant electrolyte is applied to a lithium secondary battery containing an electrode of the present invention, the flame retardant electrolyte can be easily impregnated into the coating, so that a uniform reaction can occur in the entire electrode, thereby improving the performance of the lithium secondary battery, such as capacity, output, and life characteristics.

[0082] Specifically, the polymer particles include one or more selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl methacrylate (PMMA), polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate and polyethylene terephthalate, but are not limited thereto. Specifically, the polymer particles may include polymethyl methacrylate.

[0083] The average particle size (D50) of the polymer particles can be 50 nanometers to 3 micrometers, specifically 50 nanometers to 2 micrometers, more specifically 50 nanometers to 1.5 micrometers, which is less than the thickness of the coating. In addition, compared with the thickness of the coating, it can be less than 1 / 100 to 1 / 3 of the thickness of the coating.

[0084] When the average particle size (D50) of the polymer particles meets the above numerical range, the dispersibility of the particles contained in the coating can be improved, and pores of appropriate size are uniformly formed in the coating, thereby improving the mobility of lithium ions. On the other hand, when the average particle size (D50) of the polymer particles is less than 50 nanometers, due to the reduced dispersibility of the particles, aggregation will occur between the particles, and the pores will be blocked by the aggregated particles, which can reduce the mobility of lithium ions and increase resistance. If the average particle size (D50) of the polymer particles is greater than 3 microns, there is a problem of the possible formation of a lithium dendrite growth path as described above.

[0085] When oxide-based solid electrolyte particles and / or ceramic particles are included together with polymer particles, the content of the polymer particles may be 10 wt % to 40 wt %, specifically 20 wt % to 40 wt %, more specifically 20 wt % to 30 wt % of the total weight of each coating layer.

[0086] Furthermore, in the coating in which oxide-based solid electrolyte particles and ceramic particles are mixed, the oxide-based solid electrolyte particles and ceramic particles may be mixed in a weight ratio of 9:1 to 1:9, and specifically, may be mixed in a weight ratio of 7:3 to 3:7.

[0087] When the above range is satisfied, the coating is most excellent in pore uniformity, heat resistance and electrolyte impregnation.

[0088] Meanwhile, each coating layer may further include one or more additives selected from the group consisting of a binder and a dispersant.

[0089] The dispersant can inhibit the excessive aggregation of polymer particles in the coating, thereby enabling the polymer particles to be effectively dispersed and present in the coating.

[0090] The dispersant may include a hydrogenated nitrile polymer. Specifically, the dispersant may be a hydrogenated nitrile copolymer, more specifically, hydrogenated nitrile rubber (H-NBR).

[0091] The hydrogenated nitrile copolymer may be a copolymer containing a structural unit derived from an α,β-unsaturated nitrile and a structural unit derived from a hydrogenated conjugated diene, or a copolymer containing a structural unit derived from an α,β-unsaturated nitrile, a structural unit derived from a conjugated diene, and a structural unit derived from a hydrogenated conjugated diene. As the α,β-unsaturated nitrile monomer, for example, acrylonitrile, methacrylonitrile, etc., any one of them alone or a mixture of two or more thereof may be used. As the conjugated diene monomer, for example, a conjugated diene monomer having 4 to 6 carbon atoms, such as 1,3-butadiene, isoprene or 2,3-methylbutadiene, any one of them alone or a mixture of two or more thereof may be used.

[0092] Based on the total weight of each coating layer, the content of the dispersant may be 1 wt % to 15 wt %, specifically 1 wt % to 10 wt %, and more specifically 1 wt % to 5 wt %. When the content of the dispersant satisfies the above range, the dispersibility of the particles contained in the coating layer can be improved, pores are uniformly formed in the coating layer, and cracks on the coating surface can be significantly reduced.

[0093] The function of the binder is to improve the adhesion between the particles of the coating and the electrodes and separator.

[0094] Examples of the binder may include one or more selected from the group consisting of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone (PVP), polytetrafluoroethylene, polyethylene, polypropylene, EPDM, sulfonated EPDM, styrene-butadiene rubber and fluororubber. Specifically, the binder may include polyvinylidene fluoride.

[0095] Based on the total weight of each coating layer, the content of the binder can be 0.1 wt % to 15 wt %, specifically 0.5 wt % to 10 wt %, more specifically 1 wt % to 5 wt %. When the content of the binder exceeds the above range and is too small, the effect of improving the adhesion cannot be expected. When the content of the binder is too large, the content of other particles is relatively reduced, which is not preferred.

[0096] The coating layer may have electrical insulation properties. In this case, the coating layer may be equivalent to a porous insulating layer, but is not limited thereto.

[0097] The coating has the property of not easily shrinking even at high temperatures. Therefore, when the coating is applied to an electrode assembly, a short circuit between the positive electrode and the negative electrode can be prevented even under high temperature conditions, thereby improving the high temperature safety of the lithium secondary battery.

[0098] <Electrode assembly>

[0099] Hereinafter, various structures of electrode assemblies will be described with reference to the accompanying drawings.

[0100] In one example, the coating may be entirely coated on the positive electrode, or entirely coated on the negative electrode, or one or more coatings may be coated on each of the positive electrode and the negative electrode.

[0101] Figure 1 and Figure 2 The structure in which the coating is formed on the positive electrode or the negative electrode is shown. Figure 3 The structure in which the coating layers are formed on the positive electrode and the negative electrode respectively is shown.

[0102] Specifically, Figure 1The electrode assembly 100 having a structure in which two or more coating layers are all formed on the positive electrode but not on the separator is schematically shown. Figure 2 The electrode assembly 200 is schematically shown to have a structure in which two or more coating layers are all formed on the negative electrode instead of the separator. Figure 3 The electrode assembly 300 having a structure in which two or more coating layers are formed, one layer is formed on the positive electrode, and one layer is formed on the negative electrode is schematically illustrated.

[0103] First, refer to Figure 1 , the electrode assembly 100 according to the embodiment of the present invention includes a negative electrode 110 , a positive electrode 120 , and a coating layer 130 .

[0104] The negative electrode 110 has a structure in which a negative electrode active material layer 112 is formed on a negative electrode current collector 111. Here, the negative electrode active material layer includes an electrode material such as a negative electrode active material, a conductive material, and a binder. In addition, although not shown in the figure, the negative electrode may be a graphite electrode made of carbon (C), or may be a metal itself.

[0105] There is no particular limitation on the negative electrode current collector 111 as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, or copper or stainless steel, aluminum-cadmium alloy, etc. whose surface is treated with one of carbon, nickel, titanium or silver, etc. can be used.

[0106] The thickness of the negative electrode current collector 111 may generally be 3 μm to 500 μm. In addition, similar to the positive electrode current collector, the negative electrode current collector may have fine concave and convex shapes formed on its surface to enhance the adhesion of the negative electrode active material. For example, the negative electrode current collector may be in various forms such as a film, a sheet, a foil, a net, a porous body, a foam body, and a non-woven fabric structure.

[0107] The negative electrode active material may include one or more selected from the group consisting of lithium metal, carbon materials capable of reversibly intercalating / deintercalating lithium ions, metals or alloys of lithium and these metals, metal composite oxides, materials that can be doped and dedoped with lithium, and transition metal oxides.

[0108] As a carbon material capable of reversibly embedding / de-embedding lithium ions, any carbon material can be used without particular limitation, as long as it is a carbon-based negative electrode active material commonly used in lithium ion secondary batteries, and as a typical example, crystalline carbon, amorphous carbon or both can be used. An example of crystalline carbon can be graphite, such as irregular, planar, flaky, spherical or fibrous natural graphite or artificial graphite, and an example of amorphous carbon can be soft carbon (low temperature calcined carbon) or hard carbon, mesophase pitch carbide and fired coke.

[0109] As the metal or an alloy of lithium and these metals, a metal or an alloy of lithium and these metals selected from the group consisting of Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.

[0110] As the metal composite oxide, one selected from the group consisting of PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, Bi2O5, Li x Fe2O3 (0 ≤ x ≤ 1), Li x WO2 (0 ≤ x ≤ 1), and Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Groups I, II, and III of the periodic table, or halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8).

[0111] The material that can be doped and de-doped with lithium can include Si, SiO x (0 < x ≤ 2), Si-Y alloy (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, but not Si), Sn, SnO2, and Sn-Y (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, but not Sn), and a mixture of SiO2 and one or more of them can be used. The element Y can be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0112] The transition metal oxide can include lithium-containing titanium composite oxide (LTO), vanadium oxide, lithium vanadium oxide, etc.

[0113] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material can be 60% by weight to 99% by weight, preferably 70% by weight to 99% by weight, more preferably 80% by weight to 98% by weight.

[0114] In addition, the conductive material is a component that can further improve the conductivity of the negative electrode active material. This type of conductive material is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, conductive materials such as carbon powders such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black or thermal black can be used; graphite powders such as natural graphite, artificial graphite or graphite with a well-developed crystal structure; conductive fibers such as carbon fibers or metal fibers; carbon fluoride powders; conductive powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives.

[0115] The conductive material may be contained in an amount of 0.1 to 10 wt %, specifically 0.5 to 5 wt %, more specifically 0.5 to 3 wt %, based on the total weight of the negative active material layer.

[0116] In addition, the binder is a component that helps to bind the conductive material, the negative electrode active material and the negative electrode current collector. Examples of the binder may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, starch, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polyethylene, polypropylene, EPDM, sulfonated EPDM, styrene-butadiene rubber, fluororubber and various copolymers thereof.

[0117] Generally, the binder may be included in an amount of 0.5 to 10 wt %, specifically 0.5 to 5 wt %, and more specifically 0.5 to 3 wt %, based on the total weight of the negative active material layer.

[0118] When the metal itself is used without forming a negative electrode active material layer on the negative electrode, it can be manufactured by physically bonding, rolling or depositing the metal on the metal film itself or the negative electrode current collector. As a deposition method, an electrodeposition method or a chemical vapor deposition method of the metal can be used.

[0119] For example, the metal film itself or the metal bonded / rolled / deposited on the negative electrode current collector may include one metal selected from the group consisting of lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In) or an alloy of two thereof.

[0120] The positive electrode 120 has a structure in which a positive electrode active material layer 122 is formed on a positive electrode collector 121. Here, the positive electrode active material layer includes electrode materials such as a positive electrode active material, a conductive material, and a binder.

[0121] The positive electrode current collector 121 is not particularly limited as long as it has high electrical conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel treated with carbon, nickel, titanium, silver, etc. on the surface can be used as the current collector.

[0122] In addition, the thickness of the positive electrode current collector 121 can generally be 3 μm to 500 μm. Fine irregularities can be formed on the entire surface of the positive electrode current collector to enhance the adhesion force of the positive electrode active material. For example, the positive electrode current collector can adopt various forms such as film, sheet, foil, net, porous body, foam body, and non-woven fabric structure.

[0123] The positive electrode active material can be a compound capable of reversibly intercalating and deintercalating lithium. Specifically, it can include lithium metal oxides containing lithium and one or more metals (such as cobalt, manganese, nickel, or aluminum). More specifically, the lithium metal oxides can include lithium manganese-based oxides (such as LiMnO2, LiMn2O4, etc.), lithium cobalt-based oxides (such as LiCoO2, etc.), lithium nickel-based oxides (such as LiNiO2, etc.), lithium nickel manganese-based oxides (such as LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-Z Ni Z O4 (where 0 < Z < 2), etc.), lithium nickel cobalt-based oxides (such as LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1, etc.), lithium manganese cobalt-based oxides (such as LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (where 0 < Z1 < 2), etc.), lithium nickel manganese cobalt-based oxides (such as Li(Ni p Co q Mn r )O2 (where 0 < p < 1, 0 < q < 1, 0 < r < 1, p + q + r = 1) or Li(Ni p1 Co q1 Mn r1 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r1 < 2, p1 + q1 + r1 = 2), etc.) or lithium nickel cobalt transition metal (M) oxides (such as Li(Ni p2 Co q2 Mn r2 M s2)O2 (where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, p2, q2, r2, and s2 are the atomic fractions of each independent element, where 0 < p2 < 1, 0 < q2 < 1, 0 < r2 < 1, 0 < s2 < 1, and p2 + q2 + r2 + s2 = 1), etc.), lithium iron phosphate (e.g., Li 1+a Fe 1-x M x (PO 4-b )X b (where M is one or more selected from Al, Mg, and Ti, X is one or more selected from F, S, and N, -0.5 ≤ a ≤ 0.5, 0 ≤ x ≤ 0.5, 0 ≤ b ≤ 0.1), etc., and any one or more than two of its compounds can be used.

[0124] Among these compounds, in terms of improving the capacity characteristics and stability of the battery, lithium metal oxides can include LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxides (e.g., Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), lithium nickel cobalt aluminum oxides (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.) or lithium nickel manganese cobalt aluminum oxides (e.g., Li(Ni 0.86 Co 0.05 Mn 0.07 Al 0.02 )O2), or lithium iron phosphate (e.g., LiFePO4), etc., and any one or a mixture of two or more of them can be used.

[0125] Based on the total weight of the positive electrode active material layer, the content of the positive electrode active material can be 60 wt% to 99 wt%, preferably 70 wt% to 99 wt%, more preferably 80 wt% to 98 wt%.

[0126] The description of the conductive material and the binder is the same as that of the negative electrode active material layer.

[0127] At the same time, a coating layer 130 is formed between the positive electrode 120 and the negative electrode 110 .

[0128] Here, the coating layer 130 includes a first coating layer 132 facing the negative electrode 110. In addition, it also includes a second coating layer 131 facing the positive electrode 120.

[0129] At this time, the coating layer may be formed by first coating the second coating layer 131 on the positive electrode 120 and then coating the first coating layer 132 on the second coating layer 131 .

[0130] At this time, the thickness t1 and t22 of each of the first coating layer 132 and the second coating layer 131 can be 1 micron to 30 microns, specifically 3 microns to 20 microns, and more specifically 5 microns to 15 microns. In addition, the total thickness T can be 3 microns to 50 microns. If the thickness exceeds the above range and is too thin, the desired effect of the present application cannot be obtained, and the physical insulation between the positive electrode 120 and the negative electrode 110 cannot be fully ensured. If the thickness is too thick, the resistance may increase, which is not preferred.

[0131] Furthermore, the ratio of the thicknesses t1 and t2 may be 1:9 to 9:1, specifically 3:7 to 7:3, more specifically 6:4 to 4:6, and most specifically 5:5.

[0132] The ratio of thicknesses t1 and t2 can be appropriately selected according to the characteristics of the battery to be manufactured.

[0133] The total thickness T of the coating layer 130 and the respective thicknesses t1 and t2 of the coating layers 131 and 132 can be easily measured using a thickness gauge or a cross-sectional SEM photograph.

[0134] In addition, the area of ​​the coating layers 131 and 132 may be formed to have a width capable of completely insulating the positive electrode 120 and the negative electrode 110. Specifically, when the positive electrode 110 is larger than the negative electrode 120, there is no limitation as long as its area is equal to or larger than the positive electrode 120. However, in order to facilitate the manufacturing process, the coating layers 131 and 132 may be formed to have an area corresponding to the entire area of ​​the coated object.

[0135] Figure 1The structure in which the second coating layer 131 is formed on the positive electrode 120 and the first coating layer 132 is formed on the second coating layer 131 is exemplified, wherein the second coating layer 131 may be formed to have an area corresponding to the positive electrode 120, and the first coating layer 132 may be formed to have an area corresponding to the first coating layer 131. Therefore, the areas of the second coating layer 131 and the first coating layer 132 may be the same. Of course, there is no limitation on the area as long as it is an area that can insulate the positive electrode 120 and the negative electrode 110 as a whole, wherein the second coating layer 131 may be formed to be wider, and the first coating layer 132 may be formed to be smaller than the second coating layer 131. Specifically, for example, each of the coating layers 131 and 132 may be formed by coating a composition for forming the second coating layer on the positive electrode 120 and drying it, or may be formed by coating a composition for forming the first coating layer on the second coating layer 131 and drying it. At this time, the composition for forming the second coating layer and the composition for forming the first coating layer may be coated and dried separately or together, and may be formed simultaneously or sequentially in time. Alternatively, the coating layers 131 and 132 are formed as self-standing films and attached to the positive electrode 120, or may be formed by a method of applying and drying a composition for forming a second coating layer and a composition for forming a first coating layer on a substrate and then transferring them to the positive electrode 120, which method is not limited. Hereinafter, a method of forming a coating layer by applying and drying a composition for forming a first coating layer and a composition for forming a second coating layer on an electrode or a separator will be described, but it is obvious that the method is not limited thereto and may be formed by various methods.

[0136] exist Figure 1 In the embodiment, the coating 130 also replaces the diaphragm to play the role of electrical insulation.

[0137] At the same time, refer to Figure 2 , Figure 2 The electrode assembly 200 is shown having a structure in which a coating layer 230 is formed between a positive electrode 210 and a negative electrode 220. The positive electrode 220 has a structure in which a positive active material layer 222 is formed on a positive current collector 221, and the negative electrode 210 has a structure in which a negative active material layer 212 is formed on a negative current collector 211.

[0138] At this time, Figure 1 Similar to the electrode assembly 100 in FIG. 1 , the coating layer 230 further includes a second coating layer 231 facing the positive electrode 220 and a first coating layer 232 facing the negative electrode 210 .

[0139] However, Figure 1 Differently, the coating layers may be formed by first coating the first coating layer 232 on the negative electrode 210 and then coating the second coating layer 231 on the first coating layer 232 .

[0140] Therefore, in order to facilitate the manufacturing process, the areas of the coating layers 231 and 232 may be formed to correspond to the entire area of ​​the coated object and to completely insulate the positive electrode 220 and the negative electrode 210 .

[0141] Figure 2 The structure in which the first coating layer 232 is formed on the negative electrode 210 and the second coating layer 231 is formed on the second coating layer 232 is exemplified, wherein the first coating layer 232 may be formed to have an area corresponding to the negative electrode 210, and the second coating layer 231 may be formed to have an area corresponding to the first coating layer 232. Therefore, the areas of the first coating layer 232 and the second coating layer 231 may be the same. Of course, there is no limitation on the area as long as it is an area that can insulate the positive electrode 220 and the negative electrode 210 as a whole, wherein the first coating layer 232 may be formed to be wider, and the second coating layer 231 may be formed to be smaller than the first coating layer 232. Specifically, for example, each of the coating layers 231 and 232 may be formed by applying a composition for forming a first coating layer on the negative electrode 210 and drying it, or may be formed by applying a composition for forming a second coating layer on the first coating layer 232 and drying it.

[0142] Other thicknesses and methods of making the coating 230 are similar to Figure 1 Same as described in .

[0143] In addition, refer to Figure 3 In another example, an electrode assembly 300 is shown in which a coating layer 330 is formed between a positive electrode 310 and a negative electrode 320. The positive electrode 320 has a structure in which a positive electrode active material layer 322 is formed on a positive electrode collector 321, and the negative electrode 310 has a structure in which a negative electrode active material layer 312 is formed on a negative electrode collector 311.

[0144] At this time, Figure 1 Similar to the electrode assembly 100 in FIG. 1 , the coating layer 330 further includes a second coating layer 331 facing the positive electrode 320 and a first coating layer 332 facing the negative electrode 310 .

[0145] However, with Figure 1 Differently, the coatings may be formed such that the second coating layer 331 is coated on the positive electrode 320 , and the first coating layer 332 is coated on the negative electrode 310 .

[0146] Therefore, in order to facilitate the manufacturing process, the areas of the coating layers 331 and 332 may be formed to correspond to the entire area of ​​the coated object and to be able to completely insulate the positive electrode 320 and the negative electrode 310 .

[0147] Figure 3The structure in which the first coating layer 332 is formed on the negative electrode 310 and the second coating layer 331 is formed on the positive electrode 320 is disclosed as an example, wherein the first coating layer 332 may be formed to have an area corresponding to the negative electrode 310, and the second coating layer 331 may be formed to have an area corresponding to the positive electrode 320. Therefore, the first coating layer 332 may be formed wider than the second coating layer 331. Of course, the first coating layer 332 and the second coating layer 331 may be formed to have the same area. Specifically, for example, each of the coating layers 331 and 332 may be formed by applying a composition for forming a first coating layer on the negative electrode 310 and drying it, or may be formed by applying a composition for forming a second coating layer on the positive electrode 320 and drying it.

[0148] Other thicknesses and manufacturing methods of the coating 330 are similar to those described above. Figure 1 Same as described in .

[0149] Meanwhile, the electrode assembly may further include a separator.

[0150] therefore, Figures 4 to 7 Shown with Figure 1 The electrode assemblies 400 , 500 , 600 , and 700 have similar structures and further include a separator.

[0151] At this time, the coating is entirely coated on the negative electrode, or one or more coatings are coated on each of the positive electrode and the negative electrode, or the coating is entirely coated on the side of the separator facing the negative electrode, or one or more coatings may be coated on both surfaces of the separator. Figures 4 to 5 The configuration in which the coating is formed on the positive electrode and the negative electrode or only on the negative electrode is shown. Figure 6 and Figure 7 The configuration in which the coating is formed on one side or both sides of the separator is shown.

[0152] Specifically, Figure 4 Schematic diagram showing a membrane having a diaphragm inserted into Figure 3 The electrode assembly 300 includes an electrode assembly 400 having a structure between two or more coating layers. Figure 5 Schematic diagram showing a membrane having a diaphragm inserted into Figure 2 The electrode assembly 500 has a structure between the positive electrode in the electrode assembly 200 and two or more coating layers. Although not shown in the figure, Figures 1 to 3 The shape of the separator in the electrode assembly is not limited as long as it is inserted between the positive electrode and the coating or between the coatings. Figure 4 and Figure 5 This will be described as a representative example.

[0153] certainly, Figures 4 to 5 Will refer to Figures 1 to 3The description is made in terms of structure, but, as described above, the coating layer facing the electrode and the coating layer facing the separator may be different in composition as necessary.

[0154] First, refer to Figure 4 , an electrode assembly 400 having a structure in which a coating layer 430 and a separator 440 are formed between a positive electrode 410 and a negative electrode 420 is shown. The positive electrode 420 has a structure in which a positive electrode active material layer 422 is formed on a positive electrode collector 421, and the negative electrode 410 has a structure in which a negative electrode active material layer 412 is formed on a negative electrode collector 411.

[0155] At this time, the coating 430 includes Figure 3 The second coating layer 431 facing the positive electrode 420 and the first coating layer 432 facing the negative electrode 410 shown may be formed such that the second coating layer 431 may be coated on the positive electrode 420 , and the first coating layer 432 may be coated on the negative electrode 410 .

[0156] Therefore, the description about the area, manufacturing method, thickness, etc. of the coating layers 431 and 432 is the same as above. Figure 3 Same as the description in .

[0157] However, Figure 4 The electrode assembly 400 may further include a separator 440 located between the first coating layer 432 and the second coating layer 431 .

[0158] Here, the use of the separator is not particularly limited as long as it is generally used as a separator in a lithium secondary battery. In particular, a separator having high moisture retention capacity for an electrolyte solution and low resistance to the movement of electrolyte ions is preferred.

[0159] For example, as a separator, a porous polymer film made of a polyolefin polymer (e.g., ethylene homopolymer, propylene homopolymer, ethylene / butylene copolymer) or a laminated structure of two or more layers thereof can be used. In addition, conventional porous nonwoven fabrics (e.g., nonwoven fabrics formed by high melting point glass fibers, polyethylene terephthalate fibers, etc.) can also be used as separators.

[0160] The thickness of the separator may be 5 microns to 20 microns, specifically 5 microns to 15 microns, and more specifically 6 microns to 13 microns. If the thickness of the separator meets the above range, a short circuit between the positive electrode and the negative electrode can be effectively prevented while minimizing the resistance value of the lithium secondary battery. Therefore, the energy density of the lithium secondary battery can be prevented from decreasing and the life characteristics can be improved.

[0161] At the same time, refer to Figure 5, an electrode assembly 500 having a structure in which a coating layer 530 and a separator 540 are formed between a positive electrode 520 and a negative electrode 510 is shown. The positive electrode 520 has a structure in which a positive electrode active material layer 522 is formed on a positive electrode collector 521, and the negative electrode 510 has a structure in which a negative electrode active material layer 512 is formed on a negative electrode collector 511.

[0162] At this time, the coating layer 530 includes a first coating layer 532 facing the negative electrode 510 and a second coating layer 531 facing the separator. At this time, the second coating layer 531 is similar to the first coating layer 532 in terms of manufacturing method and structure. Figure 2 Therefore, if Figure 2 As shown, the coating layer may be formed by coating a first coating layer 532 on the negative electrode 510 , and coating a second coating layer 531 on the first coating layer 532 .

[0163] Therefore, the description about the area, manufacturing method, thickness, etc. of the coating layers 531 and 532 is the same as above. Figure 2 Same as the description in .

[0164] but, Figure 5 The electrode assembly 500 in the embodiment may further include a separator 540 located between the positive electrode 520 and the second coating layer 531 .

[0165] Meanwhile, in other examples of structures in which the electrode assembly includes a separator, Figure 6 and Figure 7 The structure in which the coating is formed on one side or both sides of the diaphragm is shown. Specifically, Figure 6 The structure in which the coating is applied to both sides of the diaphragm in the form of one or more layers is shown. Figure 7 A structure in which all coatings are applied on the side of the separator facing the negative electrode is shown.

[0166] First, refer to Figure 6 , an electrode assembly 600 having a structure in which a coating layer 630 and a separator 640 are formed between a positive electrode 620 and a negative electrode 610 is shown. Here, the positive electrode 620 has a structure in which a positive electrode active material layer 622 is formed on a positive electrode collector 621, and the negative electrode 610 has a structure in which a negative electrode active material layer 612 is formed on a negative electrode collector 611.

[0167] At this time, the coating layer 630 includes a second coating layer 631 facing the positive electrode 620 and a first coating layer 632 facing the negative electrode 610 .

[0168] However, the first coating layer 632 and the second coating layer 631 may be formed by coating both sides of the separator 640. That is, the coating layers 631 and 632 may be formed by coating the first coating layer forming composition and the second coating layer forming composition on both sides of the separator 640 and then drying.

[0169] Therefore, in order to facilitate the manufacturing process, the area of ​​the coating layers 631 and 632 can be formed to correspond to the entire area of ​​the coated object, and the area can completely insulate the positive electrode 620 and the negative electrode 610, and thus can be formed to have an area corresponding to the area of ​​the separator 640. Of course, it goes without saying that the area can also be formed to be smaller than the width of the separator 640 as long as it can completely insulate the positive electrode 620 and the negative electrode 610.

[0170] In addition, the description of the thickness of the coatings 631 and 632 is the same as above. Figure 1 Same as the description in .

[0171] At the same time, refer to Figure 7 , an electrode assembly 700 having a structure in which a coating layer 730 and a separator 740 are formed between a positive electrode 720 and a negative electrode 710 is shown. Here, the positive electrode 720 has a structure in which a positive electrode active material layer 722 is formed on a positive electrode collector 721, and the negative electrode 710 has a structure in which a negative electrode active material layer 712 is formed on a negative electrode collector 711.

[0172] At this time, the coating layer 730 includes a second coating layer 731 facing the separator 740 and a first coating layer 732 facing the negative electrode 710 .

[0173] However, the second coating layer 731 and the first coating layer 732 may be formed by being entirely applied to one surface of the diaphragm 740. That is, the composition for forming the second coating layer is first applied to one side of the diaphragm 740 and dried to form the second coating layer 831, and the composition for forming the first coating layer may be applied to the second coating layer 731 and dried to form the first coating layer 732.

[0174] Subsequently, the first coating layer 732 and the negative electrode 710 may be stacked in a direction facing each other.

[0175] Therefore, in order to facilitate the manufacturing process, the area of ​​the coatings 731 and 732 can be formed to an area corresponding to the entire area of ​​the coated object, and the area can completely insulate the positive electrode 720 and the negative electrode 710. Of course, it goes without saying that if the area is sufficient to insulate the positive electrode 720 and the negative electrode 710 as a whole, the areas of the coatings 731 and 732 can be different from each other and can be formed to be smaller than the area of ​​the separator 740.

[0176] In addition, although not shown in the figure, it goes without saying that a second coating layer 731 may be included between the positive electrode 720 and the separator 740 in FIG. 8 .

[0177] Furthermore, although two layers are shown in the above figure, it goes without saying that there is no limitation as long as the negative electrode and one or more coating layers face each other, and a configuration in which three or more layers are formed may also be included.

[0178] <Lithium Secondary Battery>

[0179] Hereinafter, a lithium secondary battery of the present invention will be described.

[0180] The lithium secondary battery of the present invention may include the electrode assembly, an electrolyte, and a battery case.

[0181] The electrolyte may be a non-aqueous lithium electrolyte containing a non-aqueous organic solvent and a lithium salt, or may be a flame retardant electrolyte containing a flame retardant solvent having no detectable flash point (substantially non-flammable) or a flash point of 100° C. or higher and a lithium salt.

[0182] As the non-aqueous organic solvent for the non-aqueous lithium electrolyte, for example, aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, 4-methyl-1,3-dioxane, ether, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate, ethyl propionate, etc. can be used.

[0183] However, when the non-aqueous lithium electrolyte contains such a non-aqueous organic solvent, it is a flammable solvent that is easily volatile and ignites, which may cause battery safety problems. Therefore, the electrolyte may be a flame retardant electrolyte.

[0184] The flame retardant electrolyte may be an electrolyte that is not easily volatile and does not catch fire. Therefore, when the flame retardant electrolyte is applied to a lithium secondary battery, the high temperature safety of the battery can be ensured.

[0185] Meanwhile, the flame retardant electrolyte has a problem of reducing the impregnation property of the lithium secondary battery separator (eg, polyolefin-based separator), however, the impregnation property of the flame retardant electrolyte can be improved by the coating of the present invention, so the flame retardant electrolyte can be used.

[0186] Here, the flame retardant solvent having a flash point of 100°C or above or having no flash point can serve as a medium through which ions participating in the electrochemical reaction of the battery can move. For example, the flame retardant solvent can include one or more compounds selected from sulfone compounds, nitrile compounds, phosphoric acid compounds and fluorocarbonate compounds.

[0187] The sulfone compound can be a cyclic sulfone compound or a linear sulfone compound, specifically, it can include one or more compounds selected from the group consisting of cyclopentane sulfone, tetramethylene sulfone, dibutyl sulfone, ethyl vinyl sulfone, methyl propyl sulfone, ethyl-isopropyl sulfone, ethyl-isobutyl sulfone, isopropyl-isobutyl sulfone, isopropyl-sec-butyl sulfone, and butyl-isobutyl sulfone.

[0188] The nitrile compound may include one or more compounds selected from the group consisting of acetonitrile, succinonitrile, adiponitrile, malononitrile, glutaronitrile, suberonitrile, and sebaconitrile.

[0189] The phosphoric acid compound may include one or more compounds selected from the group consisting of dimethyl methyl phosphate, trimethyl phosphate, triethyl phosphate, tributyl phosphate, diethyl ethyl phosphate, dimethyl methyl phosphate, dimethyl (2-methoxyethoxy)methylphosphonate, diethyl (2-methoxyethoxy)methylphosphonate, and triphenyl phosphate.

[0190] The fluorinated carbonate compound may include one or more compounds selected from the group consisting of bis(2,2,3,3-tetrafluoropropyl) carbonate, methyl 2,2,2-trifluoroethyl carbonate, ethyl 2,2,2-trifluoroethyl carbonate, propyl 2,2,2-trifluoroethyl carbonate, methyl 2,2,2,2',2',2'-hexafluoroisopropyl carbonate, ethyl 2,2,2,2',2',2'-hexafluoroisopropyl carbonate, bis(2,2,2-trifluoroethyl) carbonate, 2,2,2-trifluoroethyl-N,N-dimethyl carbonate, hexafluoro-isopropyl-N,N-dimethyl carbonate, 4-(2,2,3,3-tetrafluoropropoxymethyl)-[1,3]-dioxolane-2-one and bis(2,2,3,3-pentafluoropropyl) carbonate.

[0191] Lithium salts are used as media for transporting ions in lithium secondary batteries. Lithium salts may include, for example, Li + as a cation, and may contain one or more selected from the group consisting of: F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - , B 10 Cl 10 - 、AlCl4 - 、AlO2 - PF6 - CF3SO3 - 、CH3CO2 - CF3CO2- 、AsF6 - 、SbF6 - 、CH3SO3 - 、(CF3CF2SO2)2N - 、(CF3SO2)2N - 、(FSO2)2N - 、BF2C2O4 - , BC4O8 - PF4C2O4 - PF2C4O8 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - CF3(CF2)7SO3 - and SCN - .

[0192] Specifically, the lithium salt may include a lithium salt selected from the group consisting of LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10 , LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiFSI (lithium bis(fluorosulfonyl)imide, LiN(SO2F)2), LiBETI (lithium bis(perfluoroethanesulfonyl)imide, LiN(SO2CF2CF3)2) and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, LiN(SO2CF3)2) or a mixture of two or more thereof, however, from the perspective of excellent stability, it is preferred to contain LiN(SO2CF3)2.

[0193] In addition, lithium salts commonly used in lithium secondary battery electrolytes may be used without particular limitation.

[0194] The concentration of the lithium salt can be appropriately changed within a generally available range, but in order to obtain the best effect of forming a film to prevent corrosion on the surface of the electrode, the concentration of the lithium salt contained in the electrolyte can be 1 M to 3 M, specifically 1 M to 2.5 M, and more specifically 1 M to 2 M. When the concentration of the lithium salt satisfies the above range, the effect of improving the cycle characteristics of the lithium secondary battery during high temperature storage is sufficient, and the viscosity of the flame retardant electrolyte is appropriate, so that the impregnation of the flame retardant electrolyte can be improved.

[0195] In addition, in order to improve the charge and discharge characteristics, flame retardancy, etc., the electrolyte may further include pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glycol ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum chloride, etc. In some cases, a halogen-containing solvent such as carbon tetrachloride and trifluoroethylene may be further added to impart non-flammability, carbon dioxide gas may be further included to improve high temperature storage characteristics, and FEC (fluoroethylene carbonate), PRS (propylene sultone), etc. may be further included.

[0196] The lithium secondary battery of the present invention may be manufactured by housing an electrode assembly together with an electrolyte in a battery case.

[0197] The battery case may be a commonly used battery case in the art, and the outer shape is not limited depending on the battery application, for example, it may be cylindrical, prismatic, pouch-shaped or coin-shaped, but is not limited thereto.

[0198] The lithium secondary battery of another embodiment of the present invention can be used not only as a battery cell for a power source of a small device, but also preferably as a unit cell of a large and medium-sized battery module including a plurality of battery cells. Preferred examples of large and medium-sized devices include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems (ESS).

[0199] Hereinafter, the present invention will be described in detail with reference to specific examples. However, the following examples are only for the convenience of understanding the exemplary embodiments of the present invention and are not intended to limit the scope of the present invention. It is apparent to those skilled in the art that various changes and modifications may be made to the present invention without departing from the scope and spirit of the present invention, and it is self-evident that such changes and modifications are also within the scope of the appended claims.

[0200] Hereinafter, the D of the particles was measured by using a laser diffraction method based on the particle size value when the cumulative volume reached 50%. 50 The zeta potential value was measured by electrophoretic light scattering method using a dynamic light scattering device.

[0201] <Example 1>

[0202] Preparation of composition for forming first coating layer

[0203] BN (D50: 1 micrometer, Zeta potential: -38 mV) and polyvinylidene fluoride (PVDF) were put and dispersed in an N-methyl-2-pyrrolidone (NMP) solvent at a weight ratio of 90:10 to prepare a composition for forming a first coating layer.

[0204] Preparation of composition for forming second coating layer

[0205] Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (D50: 0.6 micrometer) and polyvinylidene fluoride (PVDF) were put and dispersed in an N-methyl-2-pyrrolidone (NMP) solvent at a weight ratio of 85:15 to prepare a composition for forming a second coating layer.

[0206] Negative electrode manufacturing

[0207] Next, a copper (Cu) metal film with a thickness of 20 μm was prepared as a negative electrode current collector, and graphite as a negative electrode active material, carbon black as a conductive material, carboxymethyl cellulose (CMC) as a thickener, and PVDF as a binder were placed and dispersed in water in a weight ratio of 95:1:1.5:2.5. The prepared negative electrode slurry was coated on one side of the copper metal film, dried and rolled to a thickness of 75 μm to manufacture a negative electrode.

[0208] Cathode Manufacturing

[0209] Prepare an aluminum (Al) metal film with a thickness of 15 μm as the positive electrode current collector, and use Li (Ni 0.8 Mn 0.1 Co 0.1 )O2, carbon nanotubes as a conductive material, and PVDF as a binder are put into and dispersed in NMP solvent in a weight ratio of 96:1:3, and the prepared positive electrode slurry is coated on one side of the aluminum metal film, dried and rolled to a thickness of 60 microns to manufacture the positive electrode.

[0210] Manufacturing of electrode assemblies

[0211] The composition for forming the first coating layer is coated on the negative electrode active material layer of the negative electrode to a thickness of 10 μm and dried to form the first coating layer, and the composition for forming the second coating layer is coated on the first coating layer to a thickness of 10 μm and dried to form the second coating layer.

[0212] Subsequently, a separator made of polyolefin (thickness: 15 μm) was inserted between the second coating layer and the positive electrode active material layer of the positive electrode, and Figure 5 The separator and the positive electrode active material layer are arranged as shown so as to contact each other, thereby manufacturing an electrode assembly.

[0213] Manufacturing of lithium secondary batteries

[0214] The electrode assembly was impregnated with an electrolyte in which LiN(SO2CF3)2 (LiFSI) was dissolved at 1.5 M in a flame retardant solvent, sulfolane (flash point: about 160 to 170 degrees), and was loaded into a battery case to manufacture a lithium secondary battery.

[0215] <Example 2>

[0216] In Example 1, the composition for forming a first coating layer was applied to one side of a polyolefin-made diaphragm (thickness: 15 μm) to form a first coating layer, and the composition for forming a second coating layer was applied to the other side of the diaphragm to form a second coating layer, thereby manufacturing a diaphragm assembly. Figure 6 A lithium secondary battery was manufactured in the same manner as in Example 1, except that an electrode assembly was manufactured by disposing a separator assembly between the positive electrode and the negative electrode so that the first coating layer was in facing contact with the negative electrode.

[0217] <Example 3>

[0218] In the same manner as in Example 1, a positive electrode and a negative electrode were manufactured.

[0219] Manufacturing of electrode assemblies

[0220] The composition for forming the second coating is coated on the negative electrode active material layer of the negative electrode to a thickness of 10 microns, and dried to form the second coating. The composition for forming the first coating is respectively coated on both sides of the polyolefin separator (thickness: 15 microns) to a thickness of 5 microns, and dried to form the first coating, thereby manufacturing a separator assembly.

[0221] Subsequently, the negative electrode, the separator assembly, and the positive electrode are stacked to manufacture an electrode assembly.

[0222] Manufacturing of lithium secondary batteries

[0223] The electrode assembly was impregnated with an electrolyte in which LiN(SO2CF3)2 (LiFSI) was dissolved at 1.5 M in a flame retardant solvent, sulfolane (flash point: about 160 to 170 degrees), and was loaded into a battery case to manufacture a lithium secondary battery.

[0224] <Example 4>

[0225] In the same manner as in Example 1, a positive electrode and a negative electrode were manufactured.

[0226] Manufacturing of electrode assemblies

[0227] The composition for forming the first coating layer is applied to one side of the negative electrode active material layer of the negative electrode to a thickness of 10 micrometers, and dried to form the first coating layer, and the composition for forming the second coating layer is applied to one side of the positive electrode active material layer of the positive electrode to a thickness of 10 micrometers, and dried to form the second coating layer. Then, the first coating layer and the second coating layer are arranged to face each other, thereby manufacturing an electrode assembly.

[0228] Manufacturing of lithium secondary batteries

[0229] The electrode assembly was impregnated with an electrolyte in which LiN(SO2CF3)2 (LiFSI) was dissolved at 1.5 M in a flame retardant solvent, sulfolane (flash point: about 160 to 170 degrees), and was loaded into a battery case to manufacture a lithium secondary battery.

[0230] <Comparative Example 1>

[0231] In the same manner as in Example 1, a positive electrode and a negative electrode were manufactured.

[0232] Manufacturing of electrode assemblies

[0233] The positive electrode active material layer of the positive electrode and the negative electrode active material layer of the negative electrode were arranged to face each other with a separator (thickness: 15 μm) made of polyolefin disposed therebetween. The manufacturing method of the electrode assembly was the same as that of a general lithium secondary battery.

[0234] Manufacturing of lithium secondary batteries

[0235] The electrode assembly was impregnated with an electrolyte in which LiN(SO2CF3)2 (LiFSI) was dissolved at 1.5 M in a flame retardant solvent, sulfolane, and was housed in a battery case to manufacture a lithium secondary battery.

[0236] <Comparative Example 2>

[0237] In the same manner as in Example 1, a positive electrode and a negative electrode were manufactured.

[0238] Manufacturing of electrode assemblies

[0239] The composition for forming a second coating layer of Example 1 was coated on the negative electrode active material layer of the negative electrode to a thickness of 20 μm and dried to form a coating layer.

[0240] Subsequently, a separator (thickness: 15 μm) made of polyolefin was inserted between the coating layer and the positive electrode active material layer of the positive electrode and arranged so that the separator and the positive electrode active material layer were in contact with each other, thereby manufacturing an electrode assembly.

[0241] Manufacturing of lithium secondary batteries

[0242] The electrode assembly was impregnated with an electrolyte in which LiN(SO2CF3)2 (LiFSI) was dissolved at 1.5 M in a flame retardant solvent, sulfolane, and was housed in a battery case to manufacture a lithium secondary battery.

[0243] <Comparative Example 3>

[0244] In the same manner as in Example 1, a positive electrode and a negative electrode were manufactured.

[0245] Manufacturing of electrode assemblies

[0246] In addition to using polymethyl methacrylate (PMMA) polymer particles (D50: 1 μm, zeta potential: -50 mV) instead of Li in the composition for forming the second coating layer in Example 1, 1.3 Al 0.3 Ti 1.7 Except for (PO4)3 (D50: 0.6 μm), a composition for forming a second coating layer was prepared in the same manner as in Example 1. The composition for forming a second coating layer was coated on the negative electrode active material layer of the negative electrode to a thickness of 20 μm and dried to form a coating layer.

[0247] Subsequently, a separator (thickness: 15 μm) made of polyolefin was inserted between the coating layer and the positive electrode active material layer of the positive electrode and arranged so that the separator and the positive electrode active material layer were in contact with each other, thereby manufacturing an electrode assembly.

[0248] Manufacturing of lithium secondary batteries

[0249] The electrode assembly was impregnated with an electrolyte in which LiN(SO2CF3)2 (LiFSI) was dissolved at 1.5 M in a flame retardant solvent, sulfolane, and was housed in a battery case to manufacture a lithium secondary battery.

[0250] <Comparative Example 4>

[0251] In the same manner as in Example 1, a positive electrode and a negative electrode were manufactured.

[0252] Manufacturing of electrode assemblies

[0253] In Example 1, the composition for forming the second coating is coated on the negative electrode active material layer of the negative electrode to a thickness of 10 microns, and dried to form the second coating, and the composition for forming the second coating is coated on the positive electrode active material layer of the positive electrode to a thickness of 10 microns, and dried to form the second coating.

[0254] Then, if Figure 4 As shown, a separator (thickness: 15 μm) made of polyolefin was disposed to be interposed between the second coating layers, thereby manufacturing an electrode assembly.

[0255] Manufacturing of lithium secondary batteries

[0256] The electrode assembly was impregnated with an electrolyte in which LiN(SO2CF3)2 (LiFSI) was dissolved at 1.5 M in a flame retardant solvent, sulfolane, and was housed in a battery case to manufacture a lithium secondary battery.

[0257] <Comparative Example 5>

[0258] In the same manner as in Example 1, a positive electrode and a negative electrode were manufactured.

[0259] Manufacturing of electrode assemblies

[0260] In Example 1, polymethyl methacrylate (PMMA) polymer particles (D50: 1 μm, zeta potential: -50 mV) were used instead of Li 1.3 Al 0.3 Ti 1.7 (PO4)3 (D50: 0.6 μm).

[0261] Then, in Example 1, the composition for forming the second coating is coated on the negative electrode active material layer of the negative electrode to a thickness of 10 microns, and dried to form the second coating, and the composition for forming the first coating is coated on the positive electrode active material layer of the positive electrode to a thickness of 10 microns, and dried to form the first coating.

[0262] Then, if Figure 4 As shown, a separator (thickness: 15 μm) made of polyolefin was disposed to be interposed between the first coating layer and the second coating layer to manufacture an electrode assembly.

[0263] Manufacturing of lithium secondary batteries

[0264] The electrode assembly was impregnated with an electrolyte in which LiN(SO2CF3)2 (LiFSI) was dissolved at 1.5 M in a flame retardant solvent, sulfolane, and was housed in a battery case to manufacture a lithium secondary battery.

[0265] <Experimental Example 1>

[0266] The initial capacity and discharge capacity of the lithium secondary batteries of Examples 1 to 2 and Comparative Examples 1 to 5 were measured, and the results are shown in Table 1 below.

[0267] The initial efficiency was calculated as the ratio of the discharge capacity to the charge capacity.

[0268] [Table 1]

[0269] Initial efficiency (%) Discharge capacity(mAh) Example 1 88.1 980.7 Example 2 89.1 980.7 Example 3 82.0 902.6 Example 4 88.1 980.7 Comparative Example 1 90.20% 980.7 Comparative Example 2 81.80% 889.5 Comparative Example 3 76.60% 833.6 Comparative Example 4 82.2 915.8 Comparative Example 5 77.0 851.0

[0270] With reference to Table 1, it can be confirmed that the performance of the lithium secondary battery of the present invention is better than that of Comparative Examples 2 to 5, and shows a similar level of performance to Comparative Example 1 of a lithium secondary battery not including an electrolyte layer. It can be seen that when a flame retardant solvent is used, not only is there low ion conductivity and high interface resistance between electrolyte particles, but also side reactions of materials used in the electrolyte layer in contact with the positive electrode and the negative electrode may become a problem. Therefore, when the electrolyte layer containing a material with low reactivity and a material with good electrolyte impregnation is formed as a separate layer as in the present invention, a more excellent effect can be shown.

[0271] Meanwhile, referring to Examples 1 to 4 and Comparative Example 4, it can be seen that when the negative electrode side does not contain oxide-based solid electrolyte particles but the positive electrode side contains oxide-based solid electrolyte particles, it is most preferable in terms of effect.

[0272] It will be apparent to those skilled in the art that various modifications and variations can be made in the present invention without departing from the spirit or scope of the inventions.

[0273] [Industrial Applicability]

[0274] The electrode assembly of the present invention has a coating formed into two or more layers along the stacking direction between the positive electrode and the negative electrode, and the coating contains a specific composition according to the components facing and contacting each other, thereby effectively maintaining insulation between the positive electrode and the negative electrode by providing impregnation for the electrolyte but not easily shrinking even in a high temperature environment, thereby exerting the effect of improving high temperature safety.

[0275] In addition, since the coating of the present invention itself has electrical insulation properties, it can not only play the role of a diaphragm in the absence of a diaphragm, but also prevent the diaphragm from shrinking when used with a diaphragm, further improving the electrical insulation properties, having heat resistance, and being more effective in high temperature safety.

[0276] In addition, in order to address the problem of poor performance of the battery cell due to low ionic conductivity and high interface resistance between electrolyte particles that may occur when a flame-retardant electrolyte is used together, the electrode assembly of the present invention comprises two or more coatings, so that the coating can have a more suitable composition according to the type of electrode it faces, thereby minimizing side reactions with the electrode active material and improving the performance of the lithium secondary battery.

[0277] Furthermore, when used as an electrolyte together with a flame-retardant electrolyte, not only can safety be further improved by suppressing fire, but the problem of deterioration of electrolyte impregnation that may occur due to the flame-retardant electrolyte can also be solved by including particles with surface charge in the coating.

Claims

1. An electrode assembly, comprising: A positive electrode, a negative electrode and a coating between the positive electrode and the negative electrode, in, The coating layer is formed into two or more layers in the stacking direction of the positive electrode and the negative electrode, Wherein, the coating comprises a first coating in contact with the negative electrode and a second coating not in contact with the negative electrode, the first coating contains any one of the particles selected from the following i) to iii), when the first coating contains i) or ii), the second coating contains iii), when the first coating contains iii), the second coating contains i) or ii): i) oxide solid electrolyte particles and ceramic particles with a zeta potential of 25 mV or more, ii) oxide-based solid electrolyte particles, and iii) Ceramic particles having an absolute value of zeta potential of 25 mV or more.

2. The electrode assembly according to claim 1, wherein: The oxide-based solid electrolyte particles include one or more lithium metal oxides or lithium metal phosphates selected from Nasicon-type solid electrolytes, Lisicon-type solid electrolytes, garnet-type solid electrolytes, perovskite-type solid electrolytes, and LiPON-type solid electrolytes.

3. The electrode assembly according to claim 1, wherein: The oxide solid electrolyte particles include one or more selected from the group consisting of LAGP (lithium aluminum germanium phosphate) compounds, LLZO (lithium lanthanum zirconium oxide) compounds, LATP (lithium aluminum titanium phosphate) compounds, LLZTO (lithium lanthanum zirconium tantalum oxide) compounds, LLTO (lithium lanthanum titanium oxide) compounds, LSTP (lithium silicon titanium phosphate) compounds and LGPO (lithium germanium phosphate) compounds.

4. The electrode assembly according to claim 1, wherein: The ceramic particles include one or more selected from the group consisting of BN (boron nitride), boehmite, Al2O3, TiO2, Fe2O3, SiO2, ZrO2, Co3O4, SnO2, NiO, ZnO, V2O5, LiF and MnO.

5. The electrode assembly according to claim 4, wherein: The ceramic particles include one or more selected from the group consisting of BN (boron nitride), boehmite, Al2O3 and LiF.

6. The electrode assembly according to claim 1, wherein: The second coating layer is in contact with the positive electrode surface.

7. The electrode assembly according to claim 1, wherein: The first coating comprises iii) and the second coating comprises i) or ii).

8. The electrode assembly according to claim 1, wherein: One or more of the first coating layer and the second coating layer further comprises polymer particles having an absolute value of zeta potential of 25 mV or more.

9. The electrode assembly according to claim 8, wherein: The polymer particles include one or more selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl methacrylate (PMMA), polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate and polyethylene terephthalate.

10. The electrode assembly according to claim 1, wherein: The electrode assembly further includes a separator, and the second coating layer is in facing contact with the positive electrode, the separator, or the positive electrode and the separator.

11. The electrode assembly according to claim 10, wherein: The first coating comprises iii) and the second coating comprises i) or ii).

12. The electrode assembly according to claim 10, wherein: One or more of the first coating layer and the second coating layer further comprises polymer particles having an absolute value of zeta potential of 25 mV or more.

13. The electrode assembly according to claim 12, wherein: The polymer particles include one or more selected from the group consisting of polyethylene oxide (PEO), polyphenylene sulfide (PPS), polymethyl methacrylate (PMMA), polystyrene, polyvinyl chloride, polycarbonate, polysulfone, polyethersulfone, polyetherimide, polyphenylsulfone, polyamideimide, polyimide, polybenzimidazole, polyetherketone, polyphthalamide, polybutylene terephthalate and polyethylene terephthalate.

14. The electrode assembly according to claim 1, wherein: The coatings further comprise one or more additives selected from the group consisting of a binder and a dispersant, respectively.

15. The electrode assembly according to claim 1, wherein: The thickness of the coating is 1 micron to 30 microns. 16 . A lithium secondary battery comprising the electrode assembly according to claim 1 , an electrolyte and a battery case.

17. The lithium secondary battery according to claim 16, wherein: The electrolyte is a flame retardant electrolyte comprising a lithium salt and a flame retardant solvent having a flash point of 100° C. or more or having no flash point.

18. The lithium secondary battery according to claim 17, wherein: The flame retardant solvent includes one or more compounds selected from sulfone compounds, nitrile compounds, phosphoric acid compounds and fluorocarbonate compounds.

19. The lithium secondary battery according to claim 17, wherein: The lithium salt includes LiN(SO2CF3)2.

Citation Information

Cited By

  • Diaphragm, lithium ion battery and electric device

    CN121097340A